2016
DOI: 10.1111/ajgw.12254
|View full text |Cite
|
Sign up to set email alerts
|

Developing pruning wound protection strategies for managing Eutypa dieback

Abstract: Background and Aims: Eutypa dieback is an economically important disease of grapevines and a major threat to vineyard longevity throughout the world. Developing effective preventative strategies offers the best means of control. In this study, pruning wound protectants and various spray applications were evaluated for their ability to prevent infection by ascospores of Eutypa lata. Methods and Results: Fungicides and natural alternative treatments were applied by hand to grapevine pruning wounds in winter prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Dead infected wood of grapevines, and of other hosts of E. lata which may be readily found in abandoned orchards and riparian strips, is a source of airborne ascospores which increases the potential for infection of new pruning wounds (Carter 1991, Munkvold et al 1993). Painting or spraying grapevines with a preventative treatment immediately following pruning (Ayres et al 2017) has been shown in field trials to reduce the proportion of pruning wounds infected by E. lata . Until preventative practices are universally adopted, commencing with vineyard establishment, conclusions with regard to the effect of operations, such as pruning, on the incidence and severity of disease will be better drawn from vineyards with the same management, such as the Kalimna vineyards used here, rather than vineyards of the same age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dead infected wood of grapevines, and of other hosts of E. lata which may be readily found in abandoned orchards and riparian strips, is a source of airborne ascospores which increases the potential for infection of new pruning wounds (Carter 1991, Munkvold et al 1993). Painting or spraying grapevines with a preventative treatment immediately following pruning (Ayres et al 2017) has been shown in field trials to reduce the proportion of pruning wounds infected by E. lata . Until preventative practices are universally adopted, commencing with vineyard establishment, conclusions with regard to the effect of operations, such as pruning, on the incidence and severity of disease will be better drawn from vineyards with the same management, such as the Kalimna vineyards used here, rather than vineyards of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Where cultivars are particularly susceptible to E. lata , yield decline can be expected to commence within 15 years of vineyard establishment (Munkvold et al 1994). Acceptable disease management can be achieved by application of preventative paints or sprays (Sosnowski et al 2008, Ayres et al 2017). Although there is no cure, remedial surgery can control disease if all infected material is removed (Sosnowski et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we followed the official method of European countries to evaluate pruning wounds protection products against E. lata, which suggests carrying out fungal inoculations hours after the application of preventive treatments (EPPO, 2017). Accordingly, in most of the previous pruning wound protection trials, the time elapsed between pruning wound protection and GTD fungal inoculation was 24 hours (John et al, 2005;Sosnowski et al, 2008Sosnowski et al, , 2013Halleen et al, 2010;Rolshausen et al, 2010;Kotze et al, 2011;Amponsah et al, 2012;Pitt et al, 2012;Díaz and Latorre, 2013;Ayres et al, 2017;Sosnowski and Mundi, 2019). This short time between BCA treatments application and artificial fungal inoculations could also have explained the poor performance exhibited by Trichoderma-based commercial formulations in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Similar results were observed in other studies where several fungicides and BCA treatments were compared as pruning wound protectants in the same field trial. In Australian vineyards, liquid and paste fungicide formulations were more effective than Trichoderma-and Bacillus subtilis-based formulations against D. seriata and Diplodia mutila (Pitt et al, 2012), and Eutypa lata (Ayres et al, 2017) infections, respectively. Halleen et al (2010) also reported that fungicides were more effective than Trichoderma spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation